Influencing factors of neonatal red blood cell transfusion: a retrospective analysis - ZHOU Na; HE Xin; SI Yu; HOU Chen; CHEN Jialu; TANG Zhaohui (Zhongguo shuxue zazhi)
[Objective] To analyze the effects of different factors and red blood cell transfusion thresholds on the efficacy of neonatal red blood cell (RBC) transfusion, in order to provide more references for neonatal transfusions to better achieve rational and effective blood use. [Methods] A retrospective collection of data from 282 neonates who received RBC transfusions at our hospital from 2022 to 2023 was conducted, including birth weight, gestational age, number of blood transfusions, length of hospital stay, assisted ventilation during RBC transfusion, and laboratory test results before and after transfusion. SPSS software was used for statistical analysis to comprehensively analyze the impact of different factors on the efficacy of RBC transfusion in neonates. [Results] The results showed that the gestational age and weight of newborns at birth were negatively correlated with their length of hospital stay and the number of RBC transfusions during hospitalization. Newborns with younger gestational age and lower weight had longer hospital stays and more RBC transfusions during hospitalization. After administering RBCs according to the standard of 15 mL/kg, there was a statistically significant difference in the efficacy of RBC transfusion at different transfusion thresholds. In non-critical situations, RBC transfusions were ineffective when the pre-transfusion hemoglobin (Hb) level was >120 g/L. When the pre-transfusion Hb level was ≤70 g/L, RBC transfusions achieved higher efficacy in both critical and non-critical situations. [Conclusion] In critical situations, the group with pre-transfusion Hb values ≤ 70 g/L has the best RBC transfusion effect, while in non-critical situations, the group with pre-transfusion Hb levels between 81 and 90 g/L has the best RBC transfusion effect. Overall, the efficacy of RBC transfusion in non-critical situations is higher than that in critical situations.